'FEEL IT': moral cosmopolitans and the politics of the sensed in tourism. Issue 2 (3rd April 2017) - Baptista, João Afonso
ABSTRACT: Interaction is a matter of concern in all human activities. So far, this basic principle in tourism has been largely analysed and promoted through the perspective of 'the gaze'. In line with a long North-Atlantic tradition that values vision over all the other senses, tourists are too often stereotyped as gazing subjects. In this article, I present tourists in a more encompassing way: as sensing subjects. I contend that the integration of virtues such as morality and cosmopolitanism in tourism derives considerably from the deliberate inclusion of the sensory in tourism activity. These are virtues best authenticated to the tourists through multisensorial incorporation, rather than just through detached gaze. I address the importance of multisensorial experience in the constitution of tourists' cosmopolitan selves in moral terms by drawing on my own ethnographic research in the Mozambican village of Canhane.